Improving career readiness in middle school students: a systematic review of intervention approaches - Wang, Danqi; Wang, Gang (Frontiers in Psychology, 2025)
IntroductionTo address the challenges posed by the rapidly evolving career landscape on adolescent development, this study systematically reviews career intervention pathways for middle school students.MethodsIt explores the theoretical frameworks, intervention structures, evaluation systems, and outcomes associated with career interventions at middle school educational stage. Seven key terms, three databases, and four eligibility criteria were established for the review. Out of 417 articles collected, 21 were selected for comprehensive analysis.ResultsThe results indicate that the theoretical framework for middle school career interventions includes career theory and psychotherapy, with the main intervention approach group-based. The evaluation system typically relies on quasi-experimental pre- and post-test assessments. The outcomes demonstrate positive developments in career decisionmaking and career adaptability.DiscussionThis study emphasizes the critical role of career interventions and educational programs during middle school, advocating for their integration into the curriculum to support students’ career development.